Clonal variations in the activity of 3-Hydroxy-3-Methyl glutaryl-CoA reductase in bark of Hevea brasiliensis - Nair N U; George P J; Simon S P; Sreelatha S; Thomas M; Vijayakumar K R (Indian Journal of Natural Rubber Research, 1990)
HMG-CoA reductase activity in the bark of Hevea brasiliensis was estimated in four clones with contrasting yield characteristics. Significant difference in bark enzyme activity was observed between the high yielding and low yielding clones.
Keywords: Clonal variation; Hevea brasiliensis; HMG CoA reductase; Rubber biosynthetic capacity